SCARCE ANIMAL WEBSITE IN INDONESIA USING Macromedia Dreamweaver MX - Tri Agus Hartono (Jurnal Sistem Informasi, 2007)
Website of rare animals in Indonesia is created using Macromedia Dreamweaver MXprogram whose goal is to make the program a web application that displays variousinformation about the existence of rare animals found in Indonesia, which can beaccessed by all. Use Table, Link and others in making this program a facility has beenprovided by Macromedia Dreamweaver MX to facilitate in making a web page.